Understanding the Obligation to Register Former Customary Land Ownership Rights - Ignatius Pradipa Probondaru; Endang Pandamdari; Eriyantouw Wahid (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Land registration is a mandate of Law Number 5 of 1960 on the Basic Agrarian Regulations (UUPA), which aims to guarantee legal certainty and legal protection for land rights in Indonesia. Nevertheless, many lands that were formerly under customary ownership rights have not yet been registered and are only supported by administrative evidence such as girik or customary land title, letter C, or other tax documents. Such a circumstance engenders juridical ambiguity and heightens the likelihood of agrarian conflicts. Consequently, a thorough comprehension of the obligation to register lands formerly held under customary tenure is essential to achieving an orderly land administration framework. Employing a normative juridical methodology, this study integrates both statutory and conceptual approaches. Secondary data comprising primary, secondary, and tertiary legal materials were collected through library-based documentary research. The findings reveal that unregistered ex-customary lands lack robust evidentiary support for ownership, rendering their legal status susceptible to contestation. Within the national agrarian legal order, the conversion of customary rights into formal ownership rights necessitates land registration as a manifestation of state-conferred juridical recognition. Moreover, numerous impediments persist in the implementation of land registration, including low public legal consciousness, cumbersome procedural requirements, prohibitive costs, and restricted access to land administration services. Government Regulation No. 18 of 2021 mandates registration within a specified timeframe, signaling a policy-driven effort to expedite the juridification of land assets. This study affirms that accelerating registration not only fortifies legal certainty but also fosters socioeconomic stability and mitigates the emergence of land disputes.